Characterization of the First Virulent Phage Infecting Oenococcus oeni, the Queen of the Cellars - Philippe, Cécile; Chaïb, Amel; Jaomanjaka, Fety; Claisse, Olivier; Lucas, Patrick M.; Samot, Johan; Cambillau, Christian; Le Marrec, Claire (Frontiers in Microbiology, 2021)
There has been little exploration of how phages contribute to the diversity of the bacterial community associated with winemaking and may impact fermentations and product quality. Prophages of Oenococcus oeni, the most common species of lactic acid bacteria associated with malolactic fermentation of wine, have been described, but no data is available regarding true virulent phages of O. oeni. The current study reports on the incidence and characterization of the first group of strictly lytic oenophages named Vinitor, isolated from the enological environment. Vinitor phages are morphologically very similar to siphoviruses infecting other lactic acid bacteria. Although widespread during winemaking, they are more abundant in musts than temperate oenophages. We obtained the complete genomic sequences of phages Vinitor162 and Vinitor27, isolated from white and red wines, respectively. The assembled genomes shared 97.6% nucleotide identity and belong to the same species. Coupled with phylogenetic analysis, our study revealed that the genomes of Vinitor phages are architecturally mosaics and represent unique combinations of modules amongst LAB infecting-phages. Our data also provide some clues to possible evolutionary connections between Vinitor and (pro)phages associated to epiphytic and insect-related bacteria.